A comprehensive, contemporary assessment of the association between the presence of hepatosteatosis and the incidence of coronary artery disease on CT coronary angiography. (11th May 2021) - Heseltine, T; Hughes, E; Packer, M; Dunne, T; Jones, R; Murray, SW; Ruzsics, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background The prevalence of non-alcoholic fatty liver disease (NAFLD) is increasing exponentially. The overall prevalence of NAFLD in the United States is predicted to increase to 33.5% of the adult population by 2030. Hepatosteatosis (HS) has been previously shown to be an independent risk factor for cardiovascular disease events. We sought to investigate the association of clinical covariates and the presence of HS and coronary artery disease (CAD) in patients referred for computed tomography coronary angiography (CTCA). Methods We performed a retrospective, observational analysis at a high-volume cardiac CT centre analysing consecutive CTCA studies. All patients referred for investigation of chest pain over a 28-month period (June 2014 to November 2016) were included. Covariates in those with CAD and patients without CAD were compared using compared using student"s t-test for continuous variables and chi-squared test for categorical variables. Logistic regression models were constructed for the multivariate analysis. Results In total there were 1499 patients referred for CTCA without prior evidence of CAD. Age, male sex, presence of hypertension and diabetes were significantly higher in those with CAD (table 1). HS evaluation was assessed in 1195 (79.7%). In the multivariate analysis significant predictors of CAD were male sex (OR 3.40, p < 0.001), family history (OR 1.90, p = 0.003), current smoking (OR 1.80, p = 0.03) and increasing age (OR 1.12, p < 0.001). The presence of HS was not associated with CAD when adjusted for risk factors (OR 1.05 CI:0.70-1.60, p = 0.80). Conclusion: We found a significant association between the increasing age, presence of hypertension, male sex, diabetes and current smoking with presence of CAD as detected by CTCA. In contrast to recent evidence HS may not be an independent risk factor for the development of the development of CAD.